Interactive E-Comic Media Based on a Scientific Approach to Improve Students' Critical Thinking Abilities on the Topic of Changes in the Form of Objects in Grade IV Elementary School - Luh Mia Gayatriyani; I Made Citra Wibawa; Putu Ari Dharmayanti (Universitas Pendidikan Ganesha, 2025)
Students’ critical thinking skills in elementary schools, especially in IPAS (Science and Social Studies) learning, remain low due to conventional teaching methods and limited use of interactive digital media. Therefore, innovative media that engage students, match their development, and support the Merdeka Curriculum and 21st-century skills are needed. This study aims to describe the design process, validity, practicality, and effectiveness of interactive e-comic media. The research used a development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Subjects included two content experts, two media experts, three teachers, and 35 fourth-grade students. Instruments consisted of validity and practicality questionnaires and critical thinking essay tests, analyzed quantitatively and qualitatively. Results showed content validity index of 3.85 and media validity of 3.78, both rated very good; practicality scores were 95.83% from teachers and 98.61% from students, also very good; effectiveness was proven with a significance value of 0.000 (<0.05), indicating the media effectively improves critical thinking skills. In conclusion, the interactive e-comic media is valid, practical, and effective, and it enhances learning quality while helping teachers implement the Merdeka Curriculum.